The impact of Gender Variable on the Importance of Artificial Intelligence in UAE society - Alketbi , Saeed; Alomosh, Ahmad (Al-Adab Journal, 2024)
This study aimed to reveal the impact of gender variable on the importance of artificial intelligence in the UAE society. The study used the statistical method which was used as a tool for collecting data. The sample of the study consisted of (1000) workers in the Ministry of Interior in the United Arab Emirates. The results concluded that the field of the importance of artificial intelligence came with an arithmetic average of (2.79) and with a high degree and the field of security quality of life came with an arithmetic average of (2.85) and with a high degree. The results appeared that there were no statistically significant in the field of security quality of life according to the (gender) variable, while there are statistically significant differences between the averages of the responses of sample members in the field of (importance of artificial intelligence, and the total degree of the scale) according to the (gender) variable, and the differences came in favor of male gender.